2013
DOI: 10.1007/s11999-013-3148-7
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Arthroscopic Transosseous Suture Repair of the Rotator Cuff without the Use of Anchors

Abstract: BackgroundAlthough arthroscopic anchor suturing is commonly used for rotator cuff repair and achieves good results, certain shortcomings remain, including difficulty with reoperation in cases of retear, anchor dislodgement, knot impingement, and financial cost. In 2005, we developed an anchorless technique for arthroscopic transosseous suture rotator cuff repair.Description of TechniqueAfter acromioplasty and adequate footprint decortication, three K-wires with perforated tips are inserted through the inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 18 publications
1
99
0
3
Order By: Relevance
“…Creating these small-diameter footprint tunnels maximizes the tendon-footprint contact area, and subsequently, the bone-tendon healing area is substantially increased as compared with traditional larger anchors. This technique is ideally suited to revision cases in which previous anchor pullout has occurred or in which traditional anchors have been placed very close to one another 8,11,12 (Fig 6). Our technique involves drilling a transosseous tunnel to the axillary pouch using an ACL guide to ensure accurate and safe drill placement.…”
Section: Discussionmentioning
confidence: 99%
“…Creating these small-diameter footprint tunnels maximizes the tendon-footprint contact area, and subsequently, the bone-tendon healing area is substantially increased as compared with traditional larger anchors. This technique is ideally suited to revision cases in which previous anchor pullout has occurred or in which traditional anchors have been placed very close to one another 8,11,12 (Fig 6). Our technique involves drilling a transosseous tunnel to the axillary pouch using an ACL guide to ensure accurate and safe drill placement.…”
Section: Discussionmentioning
confidence: 99%
“…We read the article by Kuroda et al [3] with great interest. In the current study, the authors describe a novel arthroscopic transosseous technique without the use of anchors.…”
Section: To the Editormentioning
confidence: 99%
“…Kuroda et al [3] reported that the technique cannot be used in shoulders where the stump of the torn rotator cuff does not emerge across the top of the humeral head under traction. Also, operative time is rather long, ranging from 80 minutes to 176 minutes.…”
Section: To the Editormentioning
confidence: 99%
“…The overall average operating time for our procedure is approximately 105 minutes in 384 cases [4]. In order for a procedure using anchors to be less expensive, it would have to be 99 minutes shorter than that, or about 6 minutes in length (105 minutes -99 minutes = 6 minutes), which seems quite unrealistic.…”
Section: To the Editormentioning
confidence: 99%